German public attitudes towards asylum seekers, immigrants in the workplace, inflation, and local budgets: Evidence from a representative survey of the German population - Bernd Hayo; Israel García; Pierre-Méon Guillaume; Florian Neumeier; Duncan Roth (Philipps-University Marburg, School of Business and Economics, 2018)
This paper provides background information and basic descriptive statistics for a representative survey of the German population conducted on our behalf by GfK in the first quarter of 2018. The survey covers various topics, including: 1) attitudes towards asylum seekers; 2) migrating workers in the workplace; 3) inflation and monetary policy; and 4) the role played by local budgets in local voting decisions. We also collect a broad range of socio-demographic and psychological indicators.
Keywords: D72; D90; E24; E31; E58; E71; F22; H72; J61; 330; Survey evidence; Attitudes; Asylum seekers; Migrating workers; Inflation; Monetary policy; Local budgets; Germany